PENERAPAN STEM PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MELALUI LESSON STUDY - Edy Waluyo (IKIP Siliwangi, 2023)
This research aims to improve students' critical thinking skills by applying STEM-Problem Based Learning through lesson study. This research uses a lesson study approach with stages (1) plan, (2) do and (3) see. The research was carried out during three open classes with the subjects of class XI.1 students of SMAN 2 Selong totaling 34 students. The instruments used are student activity observation sheets, learning implementation observation sheets and essay tests in integral materials. Data in the form of student activities and learning outcome tests on integral materials were analyzed using descriptive statistics. The scores of students' critical thinking activities during the open class were 74.93%, 74.8% and 87.87% there was an average increase of 6.47%. Data on students' critical thinking ability scores on integral material in the first open class of 76.47% of the second open class of 88.24% and the third open class of 94.12%, there was average increase of 8.83%. The conclusion is that the application aims to improve students' critical thinking skills by applying STEM-Problem Based Learning through lesson study can increase activity and critical thinking skills.